2013
DOI: 10.1002/app.39466
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin binding and release activities moderated by interstices of trimesoyl, tridimethyl, and tridiethyl malonate first‐tier dendrimers

Abstract: Trimesoyl 1,3,5-tridimethyl malonate (TTDMM), trimesoyl 1,3,5-tridiethyl malonate (TTDEM), trimesoyl 1,3,5-tridipropyl malonate, trimesoyl 1,3,5-tridibutyl malonate, and trimesoyl 1,3,5-tridihexyl malonate first-generation dendrimers, a complete series of dialkyl malonate esters from methyl to hexyl, were synthesized by a divergent growth approach with about a 95% yield. TTDMM and TTDEM members of this series were characterized with 500-MHz NMR and Fourier transform infrared spectroscopy. The 7.469353 and 8.43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…TTDMM, TTDEM and TTDPM were synthesized according to procedures reported in our previous communication [22,23]. In brief dendrimers were synthesized by TMC core and sodium dialkyl malonate salt in 1:3 molar ratio in methanol in case of TTDMM and ethanol for the rest.…”
Section: Preparation and Characterization Of Dendrimers And Drug-dendmentioning
confidence: 99%
See 1 more Smart Citation
“…TTDMM, TTDEM and TTDPM were synthesized according to procedures reported in our previous communication [22,23]. In brief dendrimers were synthesized by TMC core and sodium dialkyl malonate salt in 1:3 molar ratio in methanol in case of TTDMM and ethanol for the rest.…”
Section: Preparation and Characterization Of Dendrimers And Drug-dendmentioning
confidence: 99%
“…Despite such extraordinary structural capabilities for MTX binding, no specific and systematic research work with TTDMM, TTDEM and TTDPM has ever been reported so far; hence our study on developing models of dendrimer-drug designing is aimed to provide an advance understanding of complexities of drug-carrier interfaces. The green method for divergent synthesis and characterization of TTDMM, TTDEM and TTDPM was reported in our previous communication [22,23]. Therefore, in this study, TTDMM, TTDEM and TTDPM with a trimesoyl chloride (TMC) core and variable dialkyl malonate esters as branching units with well-defined size were synthesized and used as drug carrier for better encapsulation of anticancer drug.…”
Section: Introductionmentioning
confidence: 96%
“…Dendrimers are relatively monodispersed and highly branched macromolecules with controlled composition and architecture consisting of three components (Figure 2(a)): a central core, interior branch cells or radial symmetry, and terminal branch cell or peripheral group [23]. Dendrimers have many void spaces for their interaction of other substances Figure 2(b) [24]. Therefore, dendrimers-NPs composite can be prepared and can be used to enhance catalytic activity.…”
Section: Dendrimers In Bioremediationmentioning
confidence: 99%
“…So very specifically the organic acids and dendrimers containing -COOH, -OH, NCO and -CH 2 in their structures could be responsible for MNP dispersion via hydrophilic, hydrophobic, instantaneous induced dipole and electrostatic interaction. In our previous work, synthesis and characterization of 1st tier dendrimers (TTDMM, TTDEM, TTDPM, TTDBM and TTDHM) have been reported with globular structure and void spaces in their molecular framework with strong drug binding ability [29,30]. Their surface functionality and void spaces with variable dialkyl chain have initiated intermolecular interaction with MNPs.…”
Section: Introductionmentioning
confidence: 98%